2021
DOI: 10.1186/s11671-021-03518-x
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate/Polycaprolactone/Gelatin Electrospun Nanofibers with Antithrombogenicity and Enhanced Endothelial Cell Affinity as a Potential Scaffold for Blood Vessel Tissue Engineering

Abstract: Electrospun polymer nanofibers have gained much attention in blood vessel tissue engineering. However, conventional nanofiber materials with the deficiencies of slow endothelialization and thrombosis are not effective in promoting blood vessel tissue repair and regeneration. Herein, biomimetic gelatin (Gt)/polycaprolactone (PCL) composite nanofibers incorporating a different amount of chondroitin sulfate (CS) were developed via electrospinning technology to investigate their effects on antithrombogenicity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Gelatin and polyurethane coating fabrics showed the characteristic peaks at 2940 cm −1 and 3310 cm −1 due to the stretch vibration of C-H and -OH groups, respectively [ 40 ]. In the fingerprint region, new characteristic peaks appeared at 1650 cm −1 and 1540 cm −1 in the spectrogram of gelatin coating fabric, which was attributed to the stretch vibration of amide bond and bending vibrations of amide double bond [ 41 , 42 ]. Compared with the spectroscopy of gelatin coating, the PU-Gel coating fabric spectroscopy showed stronger characteristic peaks at 1650 cm −1 and 1540 cm −1 , which was attributed to the mixture effect of polyurethane and gelatin [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Gelatin and polyurethane coating fabrics showed the characteristic peaks at 2940 cm −1 and 3310 cm −1 due to the stretch vibration of C-H and -OH groups, respectively [ 40 ]. In the fingerprint region, new characteristic peaks appeared at 1650 cm −1 and 1540 cm −1 in the spectrogram of gelatin coating fabric, which was attributed to the stretch vibration of amide bond and bending vibrations of amide double bond [ 41 , 42 ]. Compared with the spectroscopy of gelatin coating, the PU-Gel coating fabric spectroscopy showed stronger characteristic peaks at 1650 cm −1 and 1540 cm −1 , which was attributed to the mixture effect of polyurethane and gelatin [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The 10% CS/GEL/PCL nanofibers exhibited the best composition with enhanced cell elongation, proliferation, and attachment properties, thus proving themselves as a promising scaffold for blood vessel regeneration and repair. 336 In another investigation, Jia et al conjugated CS nanofibers with Coll to develop a potential glycosylated scaffold for smalldiameter vascular TE through reductive amination and coupled them into nanofibers through electrospinning. In vitro studies showed favorable results and enhanced mechanical strength for in vivo implantations.…”
Section: Cs-based Composites For Tissue Engineeringmentioning
confidence: 99%
“…76,77 Finally, the use of carrier particles created from natural polymers such as collagen can enhance the bioactivity of electrospun meshes fabricated from synthetic hydrophobic polymers. 78,79 This approach presents significant merits over the direct use of natural polymers for creating electrospun meshes wherein mesh mechanical properties can be severely compromised compared to meshes created from synthetic polymers. 80…”
Section: Motivation For the Use Of Particles As Gfmentioning
confidence: 99%
“…Multifactor functionalization can be used to mimic the natural tissue repair cascade whereby GFs with differential effects are sequentially released for promoting appropriate biological responses at different stages . Fifth, the incorporation of particles such as HAP can improve the tensile modulus and strength of the resulting composites, thus enhancing their applicability in bone tissue engineering. , Finally, the use of carrier particles created from natural polymers such as collagen can enhance the bioactivity of electrospun meshes fabricated from synthetic hydrophobic polymers. , This approach presents significant merits over the direct use of natural polymers for creating electrospun meshes wherein mesh mechanical properties can be severely compromised compared to meshes created from synthetic polymers …”
Section: Motivation For the Use Of Particles As Gf Carrier Vehicles W...mentioning
confidence: 99%